The effect of loading condition on the formation of residual swirl in tangentially-fired boiler - Ain Fadhil S.S.; Hasini H. (2023)
This paper presents an investigation of the behavior of reacting flow in industrial boiler with particular interest given towards the effect of boiler load conditions to the velocity and temperature distributions in the furnace chamber. The map of three-dimensional velocity in the furnace domain is manipulated with appropriate mathematical relations to give a clear and concise representation on the swirl effect under the influence of boiler loading condition. From the investigation, it is clear that the residual swirl formed in the furnace is highly influenced by the loading condition. High load condition results in strong combustion gas velocity and vice versa. As opposed to the velocity magnitudes, it is also interesting to notice that the swirl condition is hardly influence by the loading condition. 2012 American Institute of Physics.